1H, 13C and 15N resonance assignments of human DCL-1 (CD302) extracellular domain - Pospíšilová, Eliška; Kavan, Daniel; Novák, Petr; Chmelík, Josef (Biomolecular NMR assignments, 2016)
DCL-1 (CD302) is a single-pass type one transmembrane protein which is predominantly expressed on myeloid cell lines. It possess the ability of endocytosis and is assumed to play a role in cell adhesion and migration. It has been also connected to several illnesses but more on the level of mRNA than on the protein expression level. More interestingly it is alternatively expressed in the form of a fusion protein with another single-pass type one transmembrane protein DEC205 (CD205) which is normally involved in antigen-uptake and endocytosis. The fusion protein has been assigned to have altered function compared to the wild type proteins. We have performed NMR structural analysis of the 16.2 kDa extracellular domain of DCL-1 to get a better insight onto this molecule. We have been able to assign nearly 97 % of resonance frequencies for the (15)N and (13)C labeled recombinant protein. The assignments have been deposited into Biological Magnetic Resonance Data Bank under the accession number 25802.
Keywords: extracelulární prostor; Resonance assignment; C-type lectin like receptor; Lectins, C-Type; Extracellular Space; Heteronuclear NMR spectroscopy; proteinové domény; lidé; Protein NMR; lektiny typu C; Protein Domains; Nuclear Magnetic Resonance, Biomolecular; Protein Structure, Secondary; nukleární magnetická rezonance biomolekulární; receptory buněčného povrchu; sekundární struktura proteinů; Receptors, Cell Surface; DCL-1 (CD302); Humans